Implementing Process Writing Approach to Improve EFL Students’ Writing Performance in Academic Writing - Rahman, Yenni Arif; Apriyanti, Fitri; Ramadhan, Arrizqi (Attractive : Innovative Education Journal, 2024)
The research aims to improve students' essay writing skills by implementing the Process Writing Approach. Conducted as Classroom Action Research, the study involved 17 university students enrolled in a writing class. Data collection relied on writing tasks. Results indicate that with the development of appropriate procedural models, the Process Writing Approach effectively improved students' essay writing skills. Initially, before implementing the strategy, only 50 % of students achieved scores equal to or greater than C (56-70). Following Cycle I, this percentage increased to 70 %, though it fell short of the study's success criteria. Subsequently, in Cycle II, it rose to more than 80 %. This highlights the potential for improving essay writing skills, contingent upon adhering to the prescribed procedural models of the Process Writing Approach. Keywords: Process Writing Approach, Paired T-Test, Academic Writing